Enhancing Arabic Vocabulary Mastery in Vocational Students: A Flashcard-Based Approach - Ramadhani, Muhammad Adam; Ammar, Farikh Marzuki (Universitas Muhammadiyah Sidoarjo, 2024)
This study, conducted at a vocational school, aimed to enhance students' Arabic vocabulary proficiency utilizing flashcard-based methods, including the